2021
DOI: 10.1055/s-0041-1729511
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Patient Trends and Outcome: Results from a Tertiary Care Burn and Plastic Unit in Northern India

Abstract: Background Burn and trauma injuries need emergency care and resuscitation, which required uninterrupted delivery of inpatient care services during the coronavirus disease 2019 (COVID-19) pandemic. Burn patients are physiologically immunocompromised, increasing the risk of COVID-19 infection in them. This study analyzes the impact of COVID-19 pandemic on patient trends in a burn and plastic unit and assesses the effect of COVID-19 infection in burns. Methods This single-center, retrospective observational case–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
3
2
0
Order By: Relevance
“… 7 In another study conducted in India, a decrease of 37.7% was observed. 8 When we analysed burn patients by gender during the pandemic process, no significant change was found, similar to the findings of other studies. 5 , 9 …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“… 7 In another study conducted in India, a decrease of 37.7% was observed. 8 When we analysed burn patients by gender during the pandemic process, no significant change was found, similar to the findings of other studies. 5 , 9 …”
Section: Discussionsupporting
confidence: 86%
“…7 In another study conducted in India, a decrease of 37.7% was observed. 8 When we analysed burn patients by gender during the pandemic process, no significant change was found, similar to the findings of other studies. 5,9 When the effects of COVID-19 were examined by age groups in our study, the age range of 19 to 59 years was the most affected group in both periods and was not affected by the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast to our study, data from a tertiary center in New Delhi, India, showed a decrease in admissions to their center but without a change in patient outcomes. [18] Data from HICs such as the United Kingdom and the United States have shown variations in admission patterns but relatively little change in access to operative intervention or patient outcomes. [19] , [20] The heterogeneity of published reports suggests that regional pandemic factors had a significant effect on burn patient epidemiology and that some burn centers were more prepared than others to address changes in supplies, staffing, or operating room access.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported in the literature [16] . During the COVID-19 pandemic, a new mechanism of burn sustained by the usage of hand sanitiser followed by thermal exposition by cooking or lighting of a cigarette was reported, as patients were not aware of the flammable composition of hand sanitiser [17] . However, in our study population, this new mechanism was not found to cause burn injuries.…”
Section: Discussionmentioning
confidence: 99%